Attentional Bias for Imperfect Pictures in Perfectionism: An Eye-Movement Study - Li, Juan; Liu, Xiping; Yu, Bin; Tang, Weihai; Liu, Xinchun (Frontiers in Psychology, 2020)
Background: Although dot-probe paradigms have been widely used in previous studies to investigate the attentional bias of perfectionists, the exact characteristics of this bias are still unclear. Methods: In this study, eye-tracking technology was used to compare the attentional patterns of high perfectionists (HP) and low perfectionists (LP). The HP and LP groups (N=39 vs 34) completed a visual attention task in which they observed perfect vs imperfect picture pairs, during which their eye movements were recorded automatically using an EM tracking system. Results: Both the HP and LP groups showed an overall attentional bias towards imperfect pictures, as indicated by the criteria of initial visual attention orientation and attentional maintenance. There were no significant differences between the HP and LP groups during the early and middle phases of attention: both groups exhibited a longer total fixation duration on imperfect pictures than on perfect pictures. However, during the late phase of attention, the participants in the HP group diverted their attention away from the imperfect pictures and began to pay more attention to the perfect pictures. By contrast, the participants in the LP group consistently exhibited longer fixation times for imperfect pictures than the HP group during the entire duration of the stimulus. Conclusions: These findings indicate that the participants in the HP group tended to avoid imperfect stimuli during the late phase of attention; this may indicate that avoidance plays an important role in maintaining perfectionism..